Using immunotherapy to boost the abscopal effect - Ngwa, Wilfred; Hesser, Jürgen (Nature reviews. Cancer, 2018)
The abscopal effect, which is the regression of metastatic cancer at distant sites during radiotherapy, is somewhat rare but can be promoted by immunotherapy. This Opinion article describes emerging concepts and limitations of using a combination of radiotherapy and immunotherapy to boost the abscopal effect.